Synthesis and comparative study of the anticancer activity of η3-allyl palladium(II) complexes bearing N-heterocyclic carbenes as ancillary ligands. (1st August 2020) - Scattolin, Thomas; Bortolamiol, Enrica; Caligiuri, Isabella; Rizzolio, Flavio; Demitri, Nicola; Visentin, Fabiano
Graphical abstract: Fifteen new Pd(II) allyl complexes containing at least one N -heterocyclic carbene ligand and others previously published by our research group, have been tested against different tumor lines (ovarian cancer, lung cancer, colon cancer and malignant melanoma) and normal cells (human lung fibroblasts). Most of the tested compounds exhibit a much powerful antitumor activity than cisplatin on all tumor cell lines examined. Moreover, a selected number of compounds among those reported are particularly promising since exhibit a markedly lower activity toward normal cells than to cancer cells. Abstract: In this paper we report the synthesis and characterization (NMR, IR, elemental analysis and XRD) of fifteen new Pd(II) allyl complexes containing at least one N -heterocyclic carbene ligand. The synthesized compounds and others previously published by our research group, have been tested against the six tumor lines OVCAR5, A2780, A2780 cis (ovarian cancer), DLD1 (colon cancer), A549 (lung cancer) and A375 (malignant melanoma). This comparative study, involving also complexes coordinating NS and NP heteroditopic ligands, shows that most of the tested compounds exhibit a much powerful antitumor activity than cisplatin on all tumor cell lines examined. In many cases, the antiproliferative activity on the A2780 (cisplatin-sensitive) and A2780 cis (cisplatin-resistant) lines is comparable, suggesting a different mechanism of action of this class of molecules as compared to cisplatin and its derivatives. Moreover, a selected number of compounds among those reported are particularly promising since exhibit a markedly lower activity toward normal cells than to cancer cells.